Feedlot performance by month in Kansas - D.R. Ames (Kansas Agricultural Experiment Station Research Reports, 1976)
Feedlot data on 202 lots involving approximately 40,000 steers collected for five years were used to characterize feedlot performance each month of the year. Intake, average daily gain (ADG), and feed efficiency were measured. ADG was predicted for mean daily temperature (MDT).
Keywords: Cattlemen& #x27; s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Feedlot performance; Average daily gain; Intake; Feed efficiency